Intraorbital wooden foreign body detected by computed tomography and magnetic resonance imaging. Issue 1 (February 2017) - Di Gaeta, Alfredo; Giurazza, Francesco; Capobianco, Eugenio; Diano, Alvaro; Muto, Mario
To identify and localize an intraorbital wooden foreign body is often a challenging radiological issue; delayed diagnosis can lead to serious adverse complications. Preliminary radiographic interpretations are often integrated with computed tomography and magnetic resonance, which play a crucial role in reaching the correct definitive diagnosis. We report on a 40 years old male complaining of pain in the right orbit referred to our hospital for evaluation of eyeball pain and double vision with an unclear clinical history. Computed tomography and magnetic resonance scans supposed the presence of an abscess caused by a foreign intraorbital body, confirmed by surgical findings.